In vitro approach for evaluation of carob by-products as source bioactive ingredients with potential to attenuate metabolic syndrome (MetS). Issue 1 (January 2019) - Rico, D.; Martín-Diana, A.B.; Martínez-Villaluenga, C.; Aguirre, L.; Silván, J.M.; Dueñas, M.; De Luis, D.A.; Lasa, A.
Abstract: The potential bioactivities for alleviating Metabolic Syndrome associated risk factors were evaluated in carob ( Ceratonia siliqua L.) fruit by-products, i.e. seed peel, germ and pod. Carob germ and seed peel showed higher phenolic content than pod (99.72, 80.24 and 47.06 μmol GAE g −1, respectively). Pod mostly contained gallic acid and gallotannins; seed peel and germ's showed as most abundant polyphenols quercetin and apigenin derivatives. Carob pod and seed peel revealed stronger antioxidant capacities compared to germ. The strongest antihypertensive activity was found in seed peel, followed by pod and germ. Anti-inflammatory activity showed inhibition of NO production in LPS-induced macrophages, although only pod was able of reducing pro-inflammatory mediators (TNF-α andPGD2 ). Finally, fat accumulation on mature adipocytes was reduced by carob seed peel and pod extracts. This work shows the potential use of pod carob by-products as food ingredients with special relevance of carob pod for attenuating metabolic syndrome.